Use of the Airway Questionnaire 20 to Detect Changes in Quality of Life in Asthmatic Patients and its Association with the St George's Respiratory Questionnaire and Clinical Parameters. Issue 3 (2008) - Win, Thida; Pearce, Linda; Nathan, James; Cafferty, Fay; Laroche, Clare
Abstract : BACKGROUND AND OBJECTIVES: The usefulness of the Airway Questionnaire 20 (AQ20) – a short version of the St George's Respiratory Questionnaire (SGRQ) – to evaluate quality of life (QOL) in asthmatic patients following a hospital admission was assessed. METHODS: At baseline and at six months following the index admission, 135 asthmatic patients were asked to complete the AQ20 and the SGRQ. The patient's peak flow, number of subsequent asthma exacerbations and number of repeat hospital admissions were also recorded. RESULTS: The AQ20 scores ranged from 0 to 20, with a high score indicating poor QOL. The AQ20 had good coverage, with no obvious ceiling or floor effects. In multiple regression analysis, all three SGRQ components were important in predicting AQ20 scores (R 2 values were 61.9% and 73.1% for baseline and six-month scores, respectively). The AQ20 was closely correlated with the SGRQ, but not redundant when used together. Bias was low when the retest reliability of the AQ20 was evaluated using the Bland-Altman method, but variation was high (−0.64). Patients with subsequent exacerbations (n=52) had higher AQ20 scores at six-month follow-up (P=0.002). In logistic regression, the AQ20 score was closely associated with the incidence of exacerbations (OR 1.15, 95% CI 1.05 to 1.25), with a similar magnitude of association between the AQ20 and the SGRQ. The AQ20 score did not correlate with peak flow at baseline (r=−0.05; P=0.573) or at six months (r=−0.31; P=0.006), and was not responsive to changes in peak flow (r=−0.06; P=0.583). CONCLUSION: The AQ20 can be substituted for the more complicated SGRQ in the assessment of QOL in patients following a hospital admission for an asthma exacerbation.